Mentorship for Women in Medicine - LeBlanc, Constance (DALHOUSIE MEDICAL JOURNAL, 2012)
This essay includes a brief history of women in medicine and the challenges they have encountered in developing mentoring relationships. We have provided some observations from peers and of our own, on women physicians and women working in medicine at different stages of their lives and careers, and the need for vigilance and assertiveness. Family responsibilities often interfere with career goals and mentors can play a key role in strategic career management at these times. The importance of strong role models and mentors for all professionals is increasingly documented. Some tips are provided to help reduce the challenges encountered in building strong relationships with suitable mentors.